Lin28 induces resistance to anti‐androgens via promotion of AR splice variant generation. Issue 5 (30th December 2015) - Tummala, Ramakumar; Nadiminty, Nagalakshmi; Lou, Wei; Evans, Christopher P.; Gao, Allen C.
Abstract : BACKGROUND: Prostate cancer (PCa) is androgen‐dependent initially and progresses to a castration‐resistant state after androgen deprivation therapy. Treatment options for castration‐resistant PCa include the potent second‐generation anti‐androgen enzalutamide or CYP17A1 inhibitor abiraterone. Recent clinical observations point to the development of resistance to these therapies which may be mediated by constitutively active alternative splice variants of the androgen receptor (AR). METHODS: Sensitivity of LNCaP cells overexpressing Lin28 (LN‐Lin28) to enzalutamide, abiraterone, or bicalutamide was compared to that of control LN‐neo cells using cell growth assays, proliferation assays using MTT, anchorage‐dependent clonogenic ability assays and soft agar assays. Ability of LN‐Lin28 cells to maintain AR activation after treatment with enzalutamide, abiraterone, or bicalutamide was tested using immunofluorescence, Western blotting, ChIP assays, and qRT‐PCR. Importance of Lin28 in enzalutamide resistance was assessed by the downregulation of Lin28 expression in C4‐2B and 22Rv1 cells chronically treated with enzalutamide. Requirement for sustained AR signaling in LN‐Lin28 cells was examined by the downregulation of either full length AR or AR‐V7 using siRNA. RESULTS: We show that Lin28 promotes the development of resistance to currently used targeted therapeutics by enhancing the expression of AR splice variants such as AR‐V7. PCa cells overexpressing Lin28 exhibit resistance to treatment with enzalutamide, abiraterone, or bicalutamide. Downregulation of Lin28 resensitizes enzalutamide‐resistant PCa cells to enzalutamide treatment. We also show that the upregulation of splicing factors such as hnRNPA1 by Lin28 may mediate the enhanced generation of AR splice variants in Lin28‐expressing cells. CONCLUSIONS: Our findings suggest that Lin28 plays a key role in the acquisition of resistance to AR‐targeted therapies by PCa cells and establish the importance of Lin28 in PCa progression. Prostate 76:445–455, 2016 . © 2015 Wiley Periodicals, Inc.